Relaas Berbasis Online dan Implikasinya Terhadap Keabsahan Putusan ( Studi di Pengadilan Agama Brebes) - Iskandar, Dicki (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
This paper analyzes the appropriateness of online-based relationships and its implications for the validity of decisions at the Brebes Religious Court. This type of qualitative research uses empirical juridical methods. The results of the study show that online summons are said to be legal and proper with the bailiff's note that in making the summons must be in accordance with the procedure based on SEMA Regulation Number 4 of 2014 and the trial is still carried out properly, so that there is no delay in the trial which in this case is not desired by the parties. seekers of justice. The implication for the legality of the decision is that the decision is valid based on judicial power with the principle of a court which uses the principles of fast, simple and low cost.